White nights : A gentle creature ; The dream of a ridiculous man - Dostoyevsky, Fyodor, 1821-1881.; Myers, Alan (New York : Oxford University Press, 1999)
Collects three short stories by Fyodor Dostoyevsky that explore the themes of the dreamer who breaks from reality and his own ambiguous attitude to utopianism.
White nights -- A gentle creature -- Dream of a ridiculous man.
"First published as a World's Classics paperback 1995"--T.p. verso.
Cover title: Gentle creature and other stories.
Translated from the Russian.
Includes bibliographical references.
Adult
Keywords: Dostoyevsky, Fyodor, -- 1821-1881 -- Translations into English; Dostoyevsky, Fyodor, -- 1821-1881.; Short stories; Russia -- Social life and customs -- Fiction; Russia -- Social life and customs -- Fiction